Determination of Mesalamine Related Impurities from Drug Product by Reversed Phase Validated UPLC Method - Trivedi Rakshit Kanubhai; Patel Mukesh C; Kharkar Amit R (E-Journal of Chemistry)
In the present study gradient reversed-phase UPLC method was developed for simultaneous determination and separation of impurities and degradation products from drug product. The chromatographic separation was performed on acquity UPLC BEH C18 column (50 mm×2.1 mm, 1.7 µm) using gradient elution. Other UPLC parameters which were optimised are flow rate, 0.7 mL/min; detection wavelength, 220 nm; column oven temperature, 40 °C and injection volume 7 µL. Stability indicating capability was established by forced degradation experiments and separation of known degradation products. The method was validated as per International Conference on Harmonization (ICH) guideline. For all impurities and mesalamine, LOQ (limit of quantification) value was found precise with RSD (related standard daviation) of less than 2.0%. In essence, the present study provides an improved low detection limit and lower run time for evaluation of pharmaceutical quality of mesalamine delayed-release formulation. Moreover, the developed method was successfully applied for quantification of impurities and degradation products in mesalamine delayed-release formulation. The same method can also be used for determination of related substances from mesalamine drug substance.